ADVANCED PRACTICES FOR THE DEVELOPMENT OF LEADING INDUSTRIAL SECTORS IN ENSURING ECONOMIC STABILITY (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis analyzes national and international best practices in developing leading industrial sectors to ensure economic stability. The study examines the strategic role of industry in the national economy, the influence of the development of leading sectors - including energy, mechanical engineering, the chemical industry, metallurgy, and the food industry - on sustainable economic growth. The thesis highlights the possibilities of increasing added value in these sectors, expanding export potential, creating jobs, and strengthening the domestic market. Based on the experience of developed countries, effective mechanisms for implementing industrial policy, introducing innovative technologies, attracting investments, and developing public-private partnerships were also considered.
Keywords: Industries, economic stability, innovative development, leading enterprises, investments, technological renewal, public policy, competitiveness, export potential, national economy, jobs.